Strategic Planning of Stakeholders Involvement on Human Capital Support at a Holding Company - Irmawati Sri Agustini; Tungga Bhimadi Karyasa (Journal of World Conference (JWC), 2021)
The influence of Stakeholders is raised on the holding as an external and internal influence. This influence is used as input to the SWOT-analysis to be combined with the strategic planning of the holding, where the strategic planning is generated from the stages of the existing management strategy. The results of the SWOT-analysis are used as input for holding or companies in general in the formulation of Long Term Strategic Planning (LTSP). This formulation is made every 5 (five) years as a result of top management meetings consisting of: Directors, Commissioners, LTSP-teams, and several personnel from internal stakeholders. The Long Term Strategic Planning is elaborated by each directorate, including the HCS directorate, in a meeting involving the heads of the directorate work units. The results are formulated into several items in the Annual Work Program for each department. Some of these items were discussed by all members of the division within the department. The results of the division-level discussion for each work program item are generally represented as a Task Force Group from a dynamic division. The mention of the Task Force Group is used as the name for the organizational structure for the level below the department. Holding for this research is selected in a company with the main producer from mining and then processing it into basic building materials. This company was founded more than 50 years ago. Initially this company was established as a business unit for collecting community mining products. The current holding condition with 7 (seven) departments controlled by the Human Capital Support Directorate, which consists of: Human Capital Policy and Strategy Department, Human Capital Services Department, Performance Management and Talent Department, Corporate Learning and Development Department, Legal and Risk Management Department, Governance and Compliance Department, Business Process Management Department. Dynamic Task Force Groups following the results of the SWOT-analysis mentioned here include: Key Performance Indicators, Performance Excellence, counselor to the poor performance employees, and new recruitment methods.